Sports as an interdisciplinary axis of learning located in mathematical thinking in high school - Luis Alfredo Andrade Landeros (Ra Ximhai)
This research assesses the relationship between sport and mathematical thinking, allowing us to understand how this integration is perceived, valued and experienced by the graduates of the Centro de Bachillerato Tecnológico Agropecuario 116 (CBTa 116), generation 2020–2023.